2021
DOI: 10.1108/pr-04-2020-0304
|View full text |Cite
|
Sign up to set email alerts
|

Leading Machiavellians on the road to better organizational behavior

Abstract: PurposeStudies highlighting negative behavioral influences of Machiavellians are plentiful; however, those prescribing their management are scarce. Machiavellians are intelligent, adaptable and resourceful people with negative, self-serving and unethical persona traits. Their abundance in organizations poses a challenge for managers in minimizing negative consequences of Machiavellian's manipulative behaviors and tap into their true potential. Leadership can play a crucial role in this regard. This purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 81 publications
(133 reference statements)
0
11
0
Order By: Relevance
“…In fact, the mean of Mach was close to those of samples from Western countries. For example, out of a maximum score of 7, the mean Mach scores were 4.4, 3.1, and 3.3 in Shah et al (2021), Belschak et al (2018) and Belschak et al (2015), respectively, suggesting that Machiavellians are common in both China and Western countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the mean of Mach was close to those of samples from Western countries. For example, out of a maximum score of 7, the mean Mach scores were 4.4, 3.1, and 3.3 in Shah et al (2021), Belschak et al (2018) and Belschak et al (2015), respectively, suggesting that Machiavellians are common in both China and Western countries.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the mean of Mach was close to those of samples from Western countries. For example, out of a maximum score of 7, the mean Mach scores were 4.4, 3.1, and 3.3 in Shah et al. (2021), Belschak et al.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding Machiavellianism, research by both Zettler and Solga (2013) and by Shah et al (2022) reported curvilinear (inverted U‐shaped) associations with OCBs, such that intermediate levels of this trait yielded the highest OCB compared to both lower and higher levels. For other outcomes, the patterns of results were less equivocal.…”
Section: A Review Of Nonlinear Interactive Differential and Reciproca...mentioning
confidence: 99%
“…Here the idea is that (mal)adaptive leader characteristics or behaviors can mitigate or amplify the negative effects of employee dark traits on their work performance and adjustment. The leadership characteristics studied entail transformational and/or transactional leadership styles (Belschak et al, 2013; Shah et al, 2021), high involvement management style (Webster & Smith, 2019), leader dark side personality traits (Belschak et al, 2018; Wisse et al, 2015), and abusive supervision (Greenbaum et al, 2017; Hurst et al, 2019; Khan et al, 2020). Reviewing these studies yields a complex picture of how leadership styles and behaviors interact with employee dark triad traits.…”
Section: A Review Of Nonlinear Interactive Differential and Reciproca...mentioning
confidence: 99%
“…strategies and leadership styles for managing Machiavellians (Shah et al, 2021;Linuesa-Langreo et al, 2019). Like leader Machiavellianism, high Machiavellianism in employees is also linked to negative work behaviours, emotions and attitudes (such as stress and burnout).…”
Section: Machiavellian Leadership In Organisationsmentioning
confidence: 99%